Modeling the 1783-1784 Laki eruption in Iceland: 2. Climate impacts - Zambri, Brian (author); Robock, Alan (author); Mills, Michael J. (author); Schmidt, Anja (author) (Journal of Geophysical Research: Atmospheres, 2019)
The Laki eruption in Iceland, which began in June 1783, was followed by many of the typical climate responses to volcanic eruptions: suppressed precipitation and drought, crop failure, and surface cooling. In contrast to the observed cooling in 1784–1786, the summer of 1783 was anomalously warm in Western Europe, with July temperatures reaching more than 3 K above the mean. However, the winter of 1783–1784 in Europe was as cold as 3 K below the mean. While climate models generally reproduce the surface cooling and decreased rainfall associated with volcanic eruptions, model studies have failed to reproduce the extreme warming in western Europe that followed the Laki eruption. As a result of the inability to reproduce the anomalous warming, the question remains as to whether this phenomenon was a response to the eruption or merely an example of internal climate variability. Using the Community Earth System Model from the National Center for Atmospheric Research, we investigate the “Laki haze” and its effect on Northern Hemisphere climate in the 12 months following the eruption onset. We find that the warm summer of 1783 was a result of atmospheric blocking over Northern Europe, which in our model cannot be attributed to the eruption. In addition, the extremely cold winter of 1783–1784 was aided by an increased likelihood of an El Niño after the eruption. Understanding the causes of these anomalies is important not only for historical purposes but also for understanding and predicting possible climate responses to future high‐latitude volcanic eruptions.